Fundamentals of infrared detector materials - Kinch, Michael A. (SPIE Press, 2007)
The choice of available infrared (IR) detectors for insertion into modern IR systems is both large and confusing. The purpose of this volume is to provide a technical database from which rational IR detector selection criteria evolve, and thus clarify the options open to the modern IR system designer. Emphasis concentrates mainly on high-performance IR systems operating in a tactical environment, although there also is discussion of both strategic environments and low- to medium-performance system requirements.
Keywords: Infrared detectors -- Materials.; elektronické knihy; electronic books